PENGARUH DEBT TO EQUITY RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSETS PADA PT ACE HARDWARE INDONESIA Tbk PERIODE 2013-2023 - Ifan Fahriyan, Ade; Sari Budhiarjo, Intan (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether the Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) have an effect or not on Return on Assets (ROA) at PT Ace Hardware Indonesia Tbk for the period 2013-2023. This study uses a descriptive method with a quantitative approach. The population used in this study is the financial statements of PT Ace Hardware Indonesia Tbk for the period 2013-2023. The data analysis method uses descriptive statistical analysis tests, classical assumption tests, multiple linear regression tests, determination coefficient tests, and hypothesis tests with the help of the SPSS version 26 program. The results of the study showed that the t-test of the Debt to Equity Ratio was -0.880 <2.26216 and a significance value of 0.405> 0.05, meaning that the Debt to Equity Ratio partially has no significant effect on Return on Assets. tcount Total Asset Turnover of 10.227 > 2.26216 and significance value of 0.000 < 0.05, meaning that Total Asset Turnover partially has a significant effect on Return on Assets. In the F test, the fcount value is 57.339 > 4.46 with a significance value < significance level of 0.000 < 0.05, meaning that it simultaneously has a significant effect on Return on Assets.